Effects of coronavirus disease 19 on the gastrointestinal tract and the potential impact on gastrointestinal toxicities during cancer treatment. Issue 3 (September 2022) - Stringer, Andrea M.
Abstract : Purpose of review: Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) has resulted in a global pandemic, with people with other conditions at greater risk of severe infection with intensified symptoms across multiple organ systems. Patients with cancer are at greater risk, and it is likely that those receiving treatment will experience greater incidence and severity of gastrointestinal toxicities, such as gastrointestinal mucositis, due to SARS-CoV-2 binding to angiotensin-converting enzyme (ACE)2 in the intestine. Recent findings: Recent studies have shown that SARS-CoV-2 patients experience gastrointestinal toxicities, and SARS-CoV-2 has capacity to infect intestinal cells through binding to ACE2 expressed in the intestine. ACE2 has a key role in intestinal homeostasis, and as such there is a concern for the impact of SARS-CoV-2 binding to ACE2 in terms of the implications for cancer treatment-induced gastrointestinal toxicities. Summary: SARS-CoV-2 is a high-risk infection for cancer patients receiving treatment. It is important to understand the mechanisms of intestinal infection with SARS-CoV-2 to determine the effect of SARS-CoV-2 infections on gastrointestinal toxicities, such as mucositis.